2019
DOI: 10.3389/fvets.2019.00203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated Grids on Growing Male Chickens Differing in Growth Performance

Abstract: Pullets, i. e., chickens of layer lines are often raised in housings equipped with perches. In contrast, broiler chickens most often are raised in a barren environment that lacks any three-dimensional structures, even though broilers also are motivated to use elevated structures. In addition, environmental enrichment may improve welfare problems in broiler chickens, such as skeletal disorders or contact dermatitis. Due to ethical reasons, currently there are attempts to fatten the male chickens of layer strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 37 publications
(49 reference statements)
2
29
1
Order By: Relevance
“…Accordingly, our results show the strains with the higher breast yield (M, and partially R1 and R2) spent a lot of time close to the feeder. Many authors [28][29][30] have shown that an increase in breast yield requires high protein and amino acid levels in feed.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our results show the strains with the higher breast yield (M, and partially R1 and R2) spent a lot of time close to the feeder. Many authors [28][29][30] have shown that an increase in breast yield requires high protein and amino acid levels in feed.…”
Section: Discussionmentioning
confidence: 99%
“…Locomotor activity was recorded at the end of each sampling period by the use of an electronic transponder system (Gantner Pigeon Systems GmbH, Schruns, Austria) as described by others (46)(47)(48). All hens were fitted with an electronic transponder that was attached to the right leg with a plastic case and cable straps and which was individually identifiable by the antennas.…”
Section: Locomotor Activity Assessmentmentioning
confidence: 99%
“…During the daytime, preening, standing, locomotion, exploration, or resting is performed, and perching birds can escape aggressive encounters on perches (7). Furthermore, enrichment of the housing environment with possibilities for perching can positively support birds' activity (8) and walking ability (9). By using non-littered elevated platforms and increasing activity, such as locomotion, chickens have less contact with litter on the chest.…”
Section: Introductionmentioning
confidence: 99%